Caribou herd dynamics : impacts of climate change on traditional and sport harvesting - Tremblay, Jean-Pierre; Festa-Bianchet, Marco; Dussault, Christian; Hins, Caroline; Brodeur, Vincent; Côté, Steeve D.; Simard, M.; Le Corre, Mael René Vincent; Taillon, Joëlle; Sharma, Sapna (Université Laval, ArcticNet Inc., 2020)
Caribou (Rangifer tarandus) are a key species in Arctic ecosystems including northern Québec and Labrador. They play a central role in the ecology of predators and the structure of Arctic plant communities. In addition, caribou provide socioeconomic and cultural benefits from subsistence and sport hunting activities. Changes in the distribution and abundance of caribou due to global climate change would have serious biological, societal, and economic implications. Direct and indirect consequences of climate change on migratory caribou herds may include alteration in habitat use, migration patterns, foraging behaviour and demography. For example, caribou may experience a further northerly shift in distribution due to several factors including longer ice-free periods, increases in snowfall and extreme weather events, alterations in the fire regime, and changes in the distribution of insects and predators. Future research by Caribou Ungava, a research group interested in the ecology of migratory caribou in the context of climate change, will address the factors outlining variations in the population dynamics of caribou, implications for survival and reproduction, as well as the response of caribou habitat to different climate change scenarios. Management efforts focusing on mitigating greenhouse gases to reduce the potential effects of climate change, preserving high quality habitat, limiting anthropogenic landscape disturbances, and managing hunting in a sustainable manner, could alleviate stressors on migratory caribou of the QuébecLabrador peninsula. 0